A Study on Drug Utilization Evaluation and Health-Related Quality of Life in Hemodialysis Patients - Farooqui, Saba; Kundu, Puja; Simon, Sandra; Amin, Savitha; Francis P, Sajan; Krishnegowda, Scandashree (Indian Journal of Pharmacy Practice)
Introduction: Hemodialysis patients have specific medical needs and challenges due to their renal failure and the need for regular dialysis treatment. These patients often experience significant physical, emotional, and social burdens associated with their condition. Studying this population can provide useful insights on the impact of drug use and its effects on their quality of life. Researchers can identify opportunities to optimise prescription regimens, eliminate side effects, and improve overall well-being by analysing the impact of drug use on their quality of life. Materials and Methods: Over the six-month period from May 2022 to October 2022, we conducted an observational and cross-sectional study on 100 patients who were admitted to the hemodialysis unit of a tertiary care teaching hospital. A well-designed data collecting form was used in conjunction with the KDQoL-36 questionnaire to record all the necessary information. Results: In a study involving 100 hemodialysis patients, it was found that 96% had co-morbidities. A total of 761 medications were prescribed, with 22.87% for female patients and 77.13% for male patients. Adverse drug reactions were observed in 52% of cases, with hyponatremia, hypokalemia, and hypoglycemia being the most common. Patients generally had an average quality of life, but some experienced below-average quality. There was a significant difference between men and women in the Physical Health component. Dry mouth and anorexia were prevalent, and adherence to food and drink limits was challenging. Cramping occurred in 62% of patients after dialysis. Patients scored worse in the physical component compared to the mental component. Conclusion: This study recognized the diversity of medications in hemodialysis patients. In conclusion, this study found that hemodialysis patients had a significant prevalence of co-morbidities, with the majority having an average quality of life. Adverse medication reactions were widespread, including hyponatraemia and hypokalaemia. Gender disparities in the physical health component were discovered. The findings of this study urge the hemodialysis unit’s practioners to create educational initiatives to raise standard of living.
Keywords: Prescribing pattern; Health-related quality of life; Hemodialysis; Drug Utilization Evaluation